Studi Implementasi Program SMK Berbasis Industri 4.0 Kontribusi menuju Indonesia Emas 2045 - Muamar Surawidarto (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to determine: (1) the framework for developing industry 4.0-based vocational schools, (2) the results of implementing this development, and (3) the relevance of the program to Indonesia Emas 2045 vision for education. The research method used was a case study of vocational schools that have implemented industry 4.0-based programs. Data was collected through observation, in-depth interviews, and questionnaires distributed to 63 participating schools. Additionally, various sources related to education policy towards the Indonesia Emas 2045 vision were consulted. The results showed that the framework for implementing industry 4.0-based vocational schools included three interventions: 1) strengthening education report card-based learning, 2) providing 4.0-based industrial practice facilities, and 3) developing physical infrastructure for industry 4.0-based TEFA. The program implementation supervision revealed that not all graduates earn wages equivalent to the minimum wage, only 18.2% of schools have link and match cooperation with DUDI to fulfill 8+i; 22% of BKK units have not been approved by the Manpower Office; all learning components have been aligned with DUDI; and 82% of school principals play an optimal role in encouraging the implementation of TEFA. The study concluded that the development of industry 4.0-based vocational schools is in line with Indonesia's Golden Age vision for education: including digitization of the educational process, adjustment of competencies required by industry 4.0 through an industry 4.0-based curriculum, activation of the Learning Management System, optimization of the role of industry practitioners in upgrading the competencies of teachers and staff, and renewal of practice room facilities and equipment.